Glycans Instructing Immunity: The Emerging Role of Altered Glycosylation in Clinical Immunology - Lyons, Jonathan J.; Milner, Joshua D.; Rosenzweig, Sergio D. (Frontiers in Pediatrics, 2015)
Protein glycosylation is an important epigenetic modifying process affecting expression, localization, and function of numerous proteins required for normal immune function. Recessive germline mutations in genes responsible for protein glycosylation processes result in congenital disorders of glycosylation (CDGs) and can have profound immunologic consequences. Genetic mutations in immune signaling pathways that affect glycosylation sites have also been shown to cause disease. Sugar supplementation and in vivo alteration of glycans by medication holds therapeutic promise for some of these disorders. Further understanding of how changes in glycosylation alter immunity may provide novel treatment approaches for allergic disease, immune dysregulation, and immunodeficiency in the future.